Characterization of PcaQ, a LysR-type transcriptional activator required for catabolism of phenolic compounds, from Agrobacterium tumefaciens - Parke, D. (Yale University, New Haven, CT.) (Journal of Bacteriology, 1996)
Previous work demonstrated that catabolism of the phenolic compounds p-hydroxybenzoate and protocatechuate via the beta-ketoadipate pathway in Agrobacterium tumefaciens is mediated by a regulatory gene, pcaQ, that acts in trans to elicit expression of many of the enzymes encoded by the pca genes. There was evidence that five pca structural genes are organized in a polycistronic operon transcribed in the order pcaDCHGB. The pcaQ gene is upstream of this operon. The activator encoded by pcaQ was novel in having the metabolite beta-carboxy-cis,cis-muconate as a coinducer. This communication reports the nucleotide sequence of pcaQ and identifies its deduced polypeptide product as a member of the LysR family of regulatory molecules. PcaQ has a calculated molecular weight of 33,546, which is consistent with the size of LysR relatives. Like many other LysR members, PcaQ serves as an activator at the level of transcription, it has a conserved amino-terminal domain, and its gene is transcribed divergently from the operon that it regulates and is subject to negative autoregulation. Studies of coinducer specificity identified an unstable pathway metabolite, gamma-carboxymuconolactone, as a second coinducer. Analysis of expression from a pcaD::lacZ promoter probe plasmid revealed that PcaQ and the coinducer exert their effect on a 133-nucleotide region upstream of pcaD. The nucleotide sequence of this region in a mutant strain constitutive for enzymes encoded by the pcaDCHGB operon identified nucleotides likely to be involved in the pcaDCHGB promoter and substantiated the inclusion of five pca structural genes in the operon